"Is there anything else you would like me to know?": Applying a trauma‐informed approach to the administration of the adverse childhood experiences questionnaire. Issue 5 (31st March 2021) - Mendel, Whitney E.; Sperlich, Mickey; Fava, Nicole M.
Abstract: Nearly ubiquitous agreement exists regarding the potentially negative impact of adverse childhood experiences (ACEs) on health and well‐being across the lifespan. This has propelled a movement across the nation for consistent screening of ACEs. Despite agreement regarding the consequences of ACEs, little research related specifically to the administration of the ACE questionnaire exists. Using data from a mixed‐methods study of first‐time mothers as means of illustration, this paper examines shortcomings of the ACE questionnaire. Participant responses revealed ambiguity with item structure, limited breadth of included events, and failure to capture the gravity of the experience. These shortcomings underscore inadequacies of the measure in accurately understanding individuals' lived experiences and call for the application of trauma‐informed (TI) values, both in its content and administration. We apply the main tenets of a TI framework to the ACE questionnaire and make recommendations for its administration, translating theoretical underpinnings of a TI approach into action.